Penerapan Model Pembelajaran Team Games Tournament untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Perencanaan dan Instalasi Sistem Audio Video di SMK Negeri 4 Gowa - Rafiuddin Rafiuddin (Jurnal Paedagogy, 2021)
This study aims to improve students' learning outcomes of Audio Video System Planning and Installation by applying the Team Games Tournament learning model in class XI TAV 1 SMK Negeri 4 Gowa. The type of research used is classroom action research (PTK), using the Kemmis & McTaggart research model which consists of four stages: planning, implementing, observing and reflecting. The four stages are carried out in two cycles. The subjects in this study were 33 people in class XI TAV 1. The instrument used was a test of learning outcomes and student observation sheet instruments. The collected data were then analyzed using descriptive statistical analysis. The results showed that the application of the Team Games Tournament learning model could improve student learning outcomes. This is evident from the increasing learning outcomes of students. Of the 33 students the initial test results with an average score of 47.15 with learning completeness as many as 6 students with a percentage of 18.18%, while what is expected is that 85% of all students achieve the Minimum Completion Criteria (KKM) with a value of ≥75. Then the learning outcomes increased by 30.30% in the learning outcomes of the first cycle test after applying the Team Games Tournament learning model, with an average value of 57.15, namely 16 students with a percentage of 48.48% learning completeness. In the second cycle test results increased 42.43% from cycle I, with an average score of students reaching 78.82, namely the completeness of learning as many as 30 students with a percentage of 90.91%. Based on the results of the study, it can be concluded that of the 33 students, more than 85% have completed their studies in the subject of Planning and Installation of Audio Video Systems with the KKM standard, namely 75.